Economic loss estimation for earthquake hazard in Istanbul - Seda Kundak (European Regional Science Association (ERSA), 2004)
Natural hazards, especially earthquakes, cause disasters when they hit large settlements such as metropolitan areas. After the first shock, the damage is counted by deaths and injuries. In a while, the destroying effects of disaster appear on economic asset of the region. Direct losses including damages in buildings and lifelines can caused non-structural or indirect losses as interruption of business activities and services. Loss estimation techniques have been developed to evaluate losses from earthquakes and other natural hazards. Recently, loss estimation models have improved due to advances in information technology and have been automated using Geographic Information Systems. The aim of this paper is to find out economic effects of probable earthquake in Istanbul. In this study, damage ratios of the most probable and the worst-case earthquake scenarios have been used in order to estimate total damage cost from destruction of houses and interruption of business activities. Despite the loss estimation model does not include monetary losses in lifeline system, centers of administration, emergency services and historical assets, the findings show that future losses, caused by a severe earthquake in Marmara Sea, will exceed the total damage cost of Kocaeli earthquake in 1999.
Keywords: 330